Granzyme A–producing T helper cells are critical for acute graft-versus-host disease - Park, Sungtae (JCI Insight, 2020)
Acute graft-versus-host disease (aGVHD) can occur after hematopoietic cell transplant in patients undergoing treatment for hematological malignancies or inborn errors. Although CD4(+) T helper (Th) cells play a major role in aGVHD, the mechanisms by which they contribute, particularly within the intestines, have remained elusive. We have identified a potentially novel subset of Th cells that accumulated in the intestines and produced the serine protease granzyme A (GrA). GrA(+) Th cells were distinct from other Th lineages and exhibited a noncytolytic phenotype. In vitro, GrA(+) Th cells differentiated in the presence of IL-4, IL-6, and IL-21 and were transcriptionally unique from cells cultured with either IL-4 or the IL-6/IL-21 combination alone. In vivo, both STAT3 and STAT6 were required for GrA(+) Th cell differentiation and played roles in maintenance of the lineage identity. Importantly, GrA(+) Th cells promoted aGVHD-associated morbidity and mortality and contributed to crypt destruction within intestines but were not required for the beneficial graft-versus-leukemia effect. Our data indicate that GrA(+) Th cells represent a distinct Th subset and are critical mediators of aGVHD.